2006
DOI: 10.1213/01.ane.0000200310.39031.1f
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetic-Induced Protection Against Lipopolysaccharide-Induced Injury in Endothelial Cells: The Role of Mitochondrial Adenosine Triphosphate-Sensitive Potassium Channels

Abstract: Lidocaine attenuates cell injury induced by ischemic-reperfusion and inflammation, although the protective mechanisms are not understood. We hypothesized that lidocaine and other amide local anesthetics protect against endothelial cell injury through activation of the mitochondrial adenosine triphosphate-sensitive potassium (mitoK(ATP)) channels. We determined the effects of amide local anesthetics (lidocaine, ropivacaine, and bupivacaine), ester local anesthetics (tetracaine and procaine), one amide analog (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
15
0
4
Order By: Relevance
“…32,33 However, these studies primarily focused on the inhibition of effects of prolonged (>24 h) cytokine exposure and used concentrations of local anesthetics up to 100,000 times higher than that used in the current study 32,33 although still much lower than concentrations required to achieve effective blockade of voltage-gated sodium channels (IC 50 of 50 to 100 μM). 34,35 Interestingly, in an earlier study, we observed that inhibition of TNFα-induced Src activation by local anesthetics occurs independently of sodium channel blockade.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 However, these studies primarily focused on the inhibition of effects of prolonged (>24 h) cytokine exposure and used concentrations of local anesthetics up to 100,000 times higher than that used in the current study 32,33 although still much lower than concentrations required to achieve effective blockade of voltage-gated sodium channels (IC 50 of 50 to 100 μM). 34,35 Interestingly, in an earlier study, we observed that inhibition of TNFα-induced Src activation by local anesthetics occurs independently of sodium channel blockade.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative analgesia associated with lidocaine's intraoperative administration compliments this action (12)(13)(14)(15)(16). Further advantages to the clinical intraoperative use of lidocaine include the protection of vital tissues, such as the brain, against periods of hypoxia (20), perhaps by activation of mitochondrial potassium ATP channels (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have also been demonstrated to exhibit significant anti-inflammatory properties [9-11]. In an earlier study of bacterial endotoxin-induced lung injury, it was shown that administration of the long-acting amide-linked local anesthetic ropivacaine attenuated endothelial cell NFκB activation and inflammatory lung injury in vivo and lung epithelial cell activation in vitro [9].…”
Section: Introductionmentioning
confidence: 99%